Peran Konsumsi Konten Religius di Media Sosial terhadap Kesejahteraan Psikologis Mahasiswa IAIN Palangkaraya - Selfi Arinie; Surawan Surawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of digital technology has brought about major changes in the communication patterns and information consumption of society, including in the religious aspect. Social media is now one of the main channels for the younger generation, especially students, to obtain inspiration and religious content that was previously only accessible through conventional media. This study aims to explore the effect of religious content consumption on social media on the psychological well-being of students at the State Islamic Institute (IAIN) Palangkaraya. This study used a mixed method approach with the participation of 30 students aged 18–24 years who were selected randomly. Data were collected through closed questionnaires and open-ended questions to explore the patterns of religious content consumption and its impact on students' psychological conditions. The results showed that consuming religious content through platforms such as TikTok and Instagram has a positive effect on students' psychological well-being. Respondents admitted to feeling calmer inwardly, more grateful, motivated to behave positively, and find meaning in life after accessing religious content such as lectures, inspirational stories, prayers, and dhikr. These findings provide important implications for educational institutions and religious content developers to utilize social media as a means of supporting mental health and spiritual growth of students strategically.